Appropriate Use Criteria for Cardiac Computed Tomography: Impact on Diagnostic Utility. Issue 5 (September 2017) - Bami, Karan; Premaratne, Manuja; Lamba, Jasmine; Yam, Yeung; Hossain, Alomgir; Keenan, Marissa; Haddad, Tony; Anand, Saipriya; Burwash, Ian G.; Ruddy, Terrence D.; Dwivedi, Girish; Chow, Benjamin J.W.
Abstract : Background: Appropriate Use Criteria (AUC) guidelines for cardiac computed tomography (CCT) were developed to limit testing to reasonable clinical settings. However, significant testing is still done for inappropriate indications. This study investigates the impact of AUC on evaluability of CCT to determine if inappropriate tests result in a greater proportion of nondiagnostic results. Methods: Investigators reviewed the medical records of 2417 consecutive patients who underwent CCT at the University of Ottawa Heart Institute. We applied the 2010 AUC and classified them as appropriate, inappropriate, or uncertain. Unclassifiable tests, as well as those with uncertain appropriateness, were excluded from the final analysis. Cardiac computed tomography results were classified as diagnostic if (1) all coronary segments were visualized, evaluable, and without obstructive stenosis; or (2) obstructive coronary artery disease with greater than 50% diameter stenosis in at least 1 coronary artery. All other test results were considered nondiagnostic. Results: Of the 1984 patients included in the final analysis, 1522 patients (76.7%) had indications that were appropriate, whereas the remaining 462 (23.3%) were inappropriate. Inappropriate tests resulted in a higher rate of nondiagnostic results compared with appropriate CCT (9.0% vs 6.2%, P = 0.034). Inappropriate tests also had significantly more studies with nonevaluable segments than appropriate tests (24.5% vs 16.4%, P < 0.001) and were more likely to reveal obstructive coronary disease than appropriate CCT (50.5% vs 32.7%, P < 0.001). Conclusions: Cardiac computed tomography done for inappropriate indications may be associated with lower diagnostic yield and could impact future downstream resource utilization and health care costs. Abstract : Supplemental digital content is available in the text.